Disulfiram potentiates the anticancer effect of cisplatin in atypical teratoid/rhabdoid tumors (AT/RT). (28th August 2020) - Jangra, Anshika; Choi, Seung Ah; Yang, Jeyul; Koh, Eun Jung; Phi, Ji Hoon; Lee, Ji Yeoun; Wang, Kyu-Chang; Kim, Seung-Ki
Abstract: Atypical teratoid/rhabdoid tumor (AT/RT) is the most malignant tumor of the central nervous system that generally occurs in young children. Despite the use of intensive multimodal therapy for AT/RT, the prognosis is still poor. The brain tumor initiating cells in AT/RT cells has been suggested as one of the challenges in AT/RT treatment. These cells have high expression of aldehyde dehydrogenase (ALDH). We investigated the combination effect of the ALDH inhibitor, disulfiram and cisplatin in the treatment of AT/RT cells. Isobologram analysis revealed that the combination therapy synergistically increases AT/RT cell death. The enzyme activity of ALDH AT/RT cells was effectively reduced by the combination therapy. We proposed that the synergistic augmentation occurs, at least partially through an increase in cleaved Poly (ADP-ribose) polymerase (PARP)-dependent apoptosis mediated by activating transcription factor 3 (ATF3). In the AT/RT mouse model, the combination therapy decreased tumor volume and prolonged survival. Immunofluorescence assay in mouse brain tissues were consistent with the expression of ATF3 and cleaved PARP. Our study demonstrates enhanced anti-cancer effect of combination therapy of disulfiram and cisplatin. This combination might provide a viable therapeutic strategy for AT/RT patients. Highlights: Isobologram analysis reveal that the combination of ALDH inhibitor, disulfiram and cisplatin synergistically increase AT/RT related cell death. Combination therapy with disulfiram and cisplatin inhibits ALDH activity and induces apoptosis in AT/RT in vitro and in vivo. The underlying mechanism of action is assumed to be increased expression of cleaved PARP with activation of ATF3.